Social media entertainment : the new intersection of Hollywood and Silicon Valley - Cunningham, Stuart; Craig, David Randolph (Postmillennial Pop Ser., 2019)
How the transformation of social media platforms and user-experience have redefined the entertainment industry In a little over a decade, competing social media platforms, including YouTube, Facebook, Twitter, Instagram, and Snapchat, have given rise to a new creative industry: social media entertainment. Operating at the intersection of the entertainment and interactivity, communication and content industries, social media entertainment creators have harnessed these platforms to generate new kinds of content separate from the century-long model of intellectual property control in the traditional entertainment industry. Social media entertainment has expanded rapidly and the traditional entertainment industry has been forced to cede significant power and influence to content creators, their fans, and subscribers. Digital platforms have created a natural market for embedded advertising, changing the worlds of marketing and communication in their wake. Combined, these factors have produced new, radically shifting demands on the entertainment industry, posing new challenges for screen regimes, media scholars, industry professionals, content creators, and audiences alike. Stuart Cunningham and David Craig chronicle the rise of social media entertainment and its impact on media consumption and production. A massive, industry-defining study with insight from over 100 industry insiders, Social Media Entertainment explores the latest transformations in the entertainment industry in this time of digital disruption.